Fetal diagnosis of left isomerism not associated with other cardiac malformations - Pires, Pedro; Mattos, Sandra; Araújo Hinrichsen, Sônia; Bravo-Valenzuela, Nathalie; Tonni, Gabriele; Araujo Júnior, Edward (Prenatal Cardiology, 2021)
Left atrial isomerism is a rare and complex congenital condition characterized by bilateral left-sidedness of atria. It is frequently associated with the loss of normal asymmetry of thoracoabdominal organs (heterotaxy syndrome) and congenital heart defects. The authors studied a rare case of left atrial isomerism with bradycardia and no associated cardiac defects. The authors reviewed important features to improve this diagnosis by applying ultrasound. A healthy pregnant woman was referred for fetal echocardiography at 20 weeks of gestation due to persistent fetal bradycardia. The fetal echocardiogram confirmed arrhythmia (fetal heart rate ranging from 95 to 100 beats per minute) with a 1:1 atrioventricular (AV) relationship and a normal AV interval time. In addition, the fetal echocardiogram showed left-sided atrial morphology with no associated cardiac defects. Absence of the hepatic segment of the inferior vena cava with azygous continuation drew attention for the diagnosis of left isomerism. The fetal heart rate remained stable until term, and a male baby was born healthy. The diagnosis of left isomerism can be very difficult to achieve prenatally, especially in the absence of associated heart defects. An interrupted inferior vena cava with azygous and hemi-azygous continuation should draw attention to this diagnosis.